El crédito bancario; una alternativa de crecimiento para las PYME´s - Alcantar Hernández, Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
This study is the end of an intense and comprehensive field research headed to resolve which the variables are and that define reflex into, of the companies. The purpose of this study is to help these companies to improve their competitiveness and to exploit the new opportunities brought by the commercial opening define reflex. In the actually situation of the nation, it’s hard of the small companies, to expansion too good as the big companies, and nothing with saw if the size of companies. It is also concluded that there is a lack of organizational capacity, indiscipline and lack of adherence at regulations for the companies. In this investigation, to bow from PYME´S (Small and Medium Enterprise), of the Information System Mexican Management the most outstanding findings show that 99.7% of the companies of Mexico, whit find of the produce the tool to aid at development, of through the credits for the best activity economic. As for the methodology of the investigation, the present study began being descriptive, this is the variables of the competitiveness they were identified and they were also defined its concept, dimension and indicators. Of here it was possible to correlate the variables to each other, to know the grade of exploit the new opportunities. The derived more important contributions of this study that are had a model of competitiveness for the companies that is expected it is from utility to other companies. The work hypotheses that were formulated in their entirety, the field work responded to the general objective and also to the four specific objectives that thought about, in the sense of contributing concrete results endorsed with opinions ant the investigator’s points of view and managers that collaborated in this investigation.

El presente estudio es la culminación de una intensa y exhaustiva investigación de campo, encaminada a determinar cuáles son las variables que definen el endeudamiento de las empresas, con el propósito de que las empresas desarrollen un impacto efectivo de la política monetaria en el crédito en base a financiamiento planeados y estructurados. En la situación actual de nuestro país, es difícil que las empresas pequeñas, se desarrollen tan bien como las grandes y no tiene nada que ver con el tamaño, las empresas grandes alguna vez tuvieron su inicio como pequeñas, es decir que cualquier pequeña empresa puede convertirse en una grande y exitosa; solo es cuestión de conocer cuáles son las áreas de ésta susceptibles de crecimiento, invertir en esas áreas y seguir creciendo, poco a poco. En esta investigación, se inclina hacia las PYME´S (Pequeñas y Medianas Empresas), que para el Sistema de Información Empresarial Mexicano (SIEM, 2002) representan más del 99.7% de la empresa en México, con el fin de generar una herramienta que les ayude a conseguir ese desarrollo; a través del crédito; que tanto nos falta, como país y como empresas. El objeto de esta investigación se basa en el estudio del tipo de proyecto y evaluación financiera de una empresa, de la que se logró conocer su capacidad de inversión, su producción, problemática y capacidad para la obtención de una mejor actividad económica. La investigación documental se enfocó al conocimiento de las principales teorías sobre los Créditos Bancarios en México. Para así, conocer el origen de endeudamiento de cada empresa de acuerdo a las características y potencialidades de las mismas y obtener como resultado su conceptualización, medición y las variables que afectan el proceso de calificación para el crédito.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2007-0059; Bancos; Financiamiento; SIEM; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5849